Comparative study of the pharmacological effects of Venarus Plus, Venarus, and Detralex on L-NAME-induced endothelial dysfunction, venous tone and platelet aggregation - Lukyanova, Yulia S.; Gureev, Vladimir V.; Kolesnichenko, Pavel D.; Danilenko, Lyudmila M.; Gudyrev, Oleg S.; Pokrovskaya, Tatyana G.; Sernov, Lev N.; Artyushkova, Elena B.; Provotorov, Vladimir Y. (AVFT – Archivos Venezolanos de Farmacología y Terapéutica, 2021)
In the present study we compared the pharmacological activity of Venarus Plus, Venarus and Detralex 1000 mg on the reversion of endothelial dysfunction (ED), and on the effect on venous tone, vascular permeability, and platelet aggregation. We used 150 Wistar male rats, weighing 180-220 g, and 80 adult albino rabbits weighing 2800 - 3200 g. Endothelial dysfunction (ED) was induced with the non-selective inhibitor of NO synthase, N-nitro-L-arginine-methyl ether (L-NAME). Functional vascular tests and biochemical markers were used to determine the reversion of the functional disorders. The anti-inflammatory effects of the drugs was evaluated in rabbits using o-xylene. The venotonic effects of the compounds was carried out on an isolated segment of the rat portal vein with Ca2+ solutions at a concentration of 0.08-1.75 mM. Our results show that the maximum daily therapeutic dose of Venarus Plus, produces a significant decrease in the ED coefficient (СED), an increase in NO synthesis, and an extended ADP-induced platelet aggregation time. The studied drugs dose-dependently reduce vascular permeability disorders caused by the application of o-xylene, which was manifested in a profound decrease the size of spots and the extension of the time interval before their onset. To study the Ca2+-mediated smooth muscle response, showed that the maximum force of vein contraction occurs with a higher dosage of drugs in the presence of a lower concentration of Ca2+, the effects of the drugs are comparable.